Research on Interband Optical Transitions in Gd2O3: Er Nanoparticles – Prospective System for Energy Convertors - A. F. Zatsepin; Yu A. Kuznetsova; M. A. Mashkovtsev; V. N. Rychkov (Advanced Aspects of Engineering Research Vol. 8, 2021)
The features of electron transitions in the region of fundamental absorption edge as well as vibrational characteristics are investigated in Gd2O3 nanoparticles doped with Er3+ ions at 0.25-8 mol% concentration. The analysis of initial reflection data is performed for cases of direct and indirect interband transitions. The dependences of corresponding energy gaps on activator concentration are obtained. The effect of strong decrease in the phonon frequency under doping of matrix with a small amount of Er3+ is found. The obtained data open new opportunities for improving the efficiency of energy conversion devices. The obtained data indicate the possibility of thermal losses minimization during the radiation conversion.